Infections Due to Acinetobacter baumannii–calcoaceticus Complex: Escalation of Antimicrobial Resistance and Evolving Treatment Options - Lynch, Joseph P., III; Clark, Nina M.; Zhanel, George G. (Seminars in Respiratory and Critical Care Medicine, 2022)
Bacteria within the genus Acinetobacter (principally A. baumannii–calcoaceticus complex [ABC]) are gram-negative coccobacilli that most often cause infections in nosocomial settings. Community-acquired infections are rare, but may occur in patients with comorbidities, advanced age, diabetes mellitus, chronic lung or renal disease, malignancy, or impaired immunity. Most common sites of infections include blood stream, skin/soft-tissue/surgical wounds, ventilator-associated pneumonia, orthopaedic or neurosurgical procedures, and urinary tract. Acinetobacter species are intrinsically resistant to multiple antimicrobials, and have a remarkable ability to acquire new resistance determinants via plasmids, transposons, integrons, and resistance islands. Since the 1990s, antimicrobial resistance (AMR) has escalated dramatically among ABC. Global spread of multidrug-resistant (MDR)-ABC strains reflects dissemination of a few clones between hospitals, geographic regions, and continents; excessive antibiotic use amplifies this spread. Many isolates are resistant to all antimicrobials except colistimethate sodium and tetracyclines (minocycline or tigecycline); some infections are untreatable with existing antimicrobial agents. AMR poses a serious threat to effectively treat or prevent ABC infections. Strategies to curtail environmental colonization with MDR-ABC require aggressive infection-control efforts and cohorting of infected patients. Thoughtful antibiotic strategies are essential to limit the spread of MDR-ABC. Optimal therapy will likely require combination antimicrobial therapy with existing antibiotics as well as development of novel antibiotic classes.
Keywords: multidrug resistance; antimicrobial resistance; Acinetobacter spp.; Acinetobacter baumannii; plasmids; clonal spread; carbapenemases